The role of School Principals in Enhancing Participatory Relationship with the Local Community in Public School in Ajloun Directorate from Teacher Perspective - Alananbeh, Rawdah Abdulkarem Abdalhalem (Journal of Educational and Psychological Sciences, 2021)
This Study aimed to identify the role of school principals in enhancing participatory relationship with the local community in public school in Ajloun directorate from teacher perspective, and to determine the effect of variables (sex, and years of experience), the researcher used the Descriptive approaches, study sample consisted of (850) Female and male teacher in Ajloun directorate, to collect data Questioner used it consisted from (25) Paragraph divided to two sector, the result shown that the level of the school principals role in enhancing participatory relationship with the local community in public school in Ajloun directorate from teacher perspective was moderated with average (3.16) , The finding also showed there is statistically significant differences at (α≤0.05) refers to principal sex (male and female) in favor of female in addition there were statistically significant differences between the teacher years of experience in favor of (10 years and more). The study recommended the necessity of holding training courses for school principals concerned with community partnership and communication mechanisms between the school and the local community.